Modeling the Medical Interview and an Approach to its Functional Invariants - Luís Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
Conducting a medical interview is a critical skill in professional practice and its acquisition by the student is a high priority training objective in medical studies. This paper aims to contribute to our professors and medical students´ counselling for performing their corresponding activities involving teaching and learning such important clinical skill. Firstly, the role of the clinical examination and interview in medical diagnosis is demonstrated; secondly, a model for conducting the interview is proposed, consisting of four phases distinguishable from each other by their particular objectives. Then, an approach to the functional invariants is performed considering those phases.